EXPLORING CREATIVITY IN VISUAL CONTENT: NAVIGATING THE DIGITAL MARKETPLACE - Mathew, Shobin; S., Jenefa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A retail merchant is a person who does business that sells goods directly to the public from a shop or store. Visual content access among the retail merchants have increased nowadays. This includes the usage of digital screens for advertising and display, access to social media through advertising etc. Since some customers choose creative contents, the merchants facilitate this using content creators. The customers prefer to go free hand for shopping requirements and mobile phones are always with them that help in digital payments. Scanning of QR code is very common nowadays. The merchants starting using computers for storing account related data. This will help in making transactions systematic. Analysis of business is also easier by storing data in computers. Digital screens are common which facilitate running messages that show various offers provided by the shops. This is dynamic and has better visual impact than traditional posters. This study investigates the extent of visual content access among retail merchants, focusing on the utilization and integration of digital tools in their business operations. Through survey with a diverse sample of retail merchants, this research explores the types of visual content adopted, the barriers to access, and the impact of visual content on business performance.